(untitled) (Journal of Nobel Medical College, 2025)
Background: Staghorn calculi, either partial or complete, present a significant urological challenge. Mini-percutaneous nephrolithotomy (mPCNL) has become a less invasive alternative to standard PCNL (sPCNL). This study evaluates the efficacy and safety of mPCNL in treating staghorn calculi. Materials and Methods: A retrospective observational study was conducted on 26 patients at Nobel Medical College Teaching Hospital for one year. Outcomes included stone-free rate (SFR), operative time, complications, and recovery. Results: The SFR was 84.6% (22/26), with failed cases associated with larger stones (mean 42.5 ± 3.2 mm) and higher Guy’s Scores. Mean operative time was 61.2 ± 12.4 minutes, increasing with stone size (p < 0.001). Complication rates were low, supporting mPCNL’s safety. Conclusion: mPCNL is effective for moderate-sized staghorn stones, offering high stone clearance with minimal morbidity